The building OER in okmindmap for innovative teaching and learning - Le Diem Bui, Le; Gi Kim, Yong; Won Ho, Won; Tthi Thu Ho, Ho; Tinh Tran, Trung; Phuong Hoang, Yen; Le Diem Trang, Bui (International Journal of Engineering and Technology, 2018)
Open educational resources (OER) are important because they help improve education across the globe, especially for developing countries. In this paper, we introduce a WebQuest that was built in OKMindmap style as suitainable OER model. We focused on how to deploy several skills of 21st century namely collaboration, communication, critical thinking, computational thinking and creativity in teaching and learning using online tools such as OKMindmap, Scratch, Youtube and Facebook to high school teacher practice in Can Tho University of Viet Nam. In the current study, OER in one OKMindmap page was built and used for learning and teaching. WebQuest in OKMindmap style was made by teachers as an assignment for 140 students in their coursework. The students' learning products in OKMindmap style called Big Book are shared to Facebook for helping our community in their long life learning. A case study investigated is a Mekong River WebQuest which asks student to do Scratch projects to present their knowledge and concerns about Mekong Delta dealing with the climate change problem and Mekong river pollution nowadays. This work shows how to apply our suggested WebQuest model effectively in schools as OER to make the teaching and learning more creative and happier for the young generation.Â Â